Humanization of Yeasts for Glycan-Type End-Products - Li, Xingjuan; Shen, Jianlie; Chen, Xingqiang; Chen, Lei; Wan, Shulin; Qiu, Xingtao; Chen, Ke; Chen, Chunmiao; Tan, Haidong (Frontiers in Microbiology, 2022)
Yeasts are often considered microorganism for producing human therapeutic glycosylated end-products at an industrial scale. However, the products with the non-humanized glycans limited their usage. Therefore, various methods to develop humanized glycosylated end-products have been widely reported in yeasts. To make full use these methods, it is necessary to summary the present researches to find the effective approaches to produce humanized products. The present researches focus on yeast species selection, glycosyltransferase deletion, expression of endoglycosidase, expression of proteins with galactosylated and or sialylated glycans. Nevertheless, the yeasts will have growth defect with low bioactivity when the key enzymes are deleted. It is necessary to express the corresponding repairing protein. Compared with N-glycosylation, the function of yeast protein O-glycosylation is not well understood. Yeast proteins have the wide variety of O-glycans in different species, and it is difficult to predict glycosylation sites, which limits the humanization of O-glycosylated yeast proteins. The future challenges include the following points: there are still many important potential yeasts have never been tried to produce glycosylated therapeutic products. Their glycosylation pathway and related mechanisms for producing humanized glycosylated proteins have rarely been reported. On the other hand, the amounts of key enzymes on glycan pathways in human beings are significantly more than those in yeasts. Therefore, there is still a challenge to produce the large body of humanized therapeutic end-products in suitable yeast species, especially the protein with complex glycans. CRISPR-Cas9 system may provide a potential approach to address the important issue.